The pharmacological effects and safety of the raw and prepared folium of Epimedium brevicornu Maxim. on improving kidney-yang deficiency syndrome and sexual dysfunction - Wang, Kai; Li, Juntao; Zheng, Xinyu; Xu, Jian; Wang, Zhe; Li, Senjie; Yang, Qiang; Wu, Yue; Yang, Dong-Hua; Yao, Shen; Zheng, Xiangwei (Frontiers in Pharmacology, 2023)
Background: Kidney-Yang deficiency syndrome (KDS) is a group of diseases related to hypothalamic-pituitary-adrenal (HPA) axis and sexual dysfunction. The folium of Epimedium brevicornu Maxim. (FEB) includes raw and prepared slices, named RFEB and PFEB, respectively. PFEB is traditionally believed to be good for tonifying kidney-Yang and improving sexual dysfunction. However, there are few studies comparing the pharmacological effects of RFEB and PFEB, and their underlying mechanisms. In this study, we aimed to compare the effects and safety of RFEB and PFEB on the HPA axis and sexual function. Additionally, the mechanisms of their roles in relation to the neuroendocrine-immune (NEI) network in the KDS model mice were explored. Methods: Male adult C57BL/6 mice were treated with corticosterone to establish a KDS mouse model, and RFEB and PFEB were administered intragastrically. Corticotropin releasing hormone (CRH), adrenocorticotropic hormone (ACTH), cyclic adenosine monophosphate (cAMP), cyclic guanosine monophosphate (cGMP), testosterone levels and oxidative damage indexes were measured. The mRNA and protein levels of CRH and ACTH in hypothalamus and pituitary, endothelial nitric oxide synthase (eNOS) and phosphodiesterase 5 (PDE5) in corpus cavernosum were examined. TNFα, IL-6, NF-κB, eNOS and PDE5 were investigated in mouse corpus cavernosum. Results: Our results showed that PFEB was more effective than RFEB in increasing corticosterone-suppressed ACTH levels, enhancing CRH levels and cAMP/cGMP ratio, and reducing oxidative damage. In vivo, PFEB significantly increased eNOS and inhibited PDE5 expression in corpus cavernosum. PFEB showed stronger protective effect on normal spleen lymphocytes from apoptosis both in vitro and in vivo. Additionally, it noticeably inhibited the levels of inflammatory cytokines in corpus cavernosum. Both RFEB and PFEB were safe and did not cause any clinical signs of toxicity in mice at the dosage of 20 times dosages of that in the Chinese Pharmacopeia. Conclusion: We demonstrated that PFEB was better than RFEB at tonifying the kidney-Yang by comparing their effects on improving the NEI network, which includes the HPA axis, immune system and corpus cavernosum. This study revealed that PFEB could significantly improve the sexual function of KDS mice by regulating the HPA axis and activating the immune system through the NEI network.